Groundwater over-exploitation and efficiency in crop production: application of data envelopment analysis - Kuppannan, Palanisami; Ranganathan, C.R.; Umetsu, C. (2011)
Groundwater over-exploitation and well failure are common in hard rock regions of south India. Groundwater scarcity influenced the farm input use and overall farm level technical efficiency. Data Envelopment Analysis (DEA) has been used to quantify the level of technical efficiency in different groundwater extraction regions of Coimbatore district of Tamil Nadu state, India. The average technical efficiency had varied from 95.55 percent in more exploited (critical) regions to 82.93 percent in less exploited (safe) regions. The scale efficiency has indicated that input use was close to the optimum level in groundwater more exploited regions compared to less exploited regions. The results had indicated that there is further scope to increase the technical efficiency among the farm groups within each groundwater extracting regions. The recommendations include adoption of a crop pattern with minimum crop failure and introduction of regular farm educational programs as well as participatory crop management programs for better use of the resources.